ChemInform Abstract: Synthesis of Sulfonamides and Sulfonic Esters via Reaction of Amines and Phenols with Thiols Using H2O2—POCl3 System. Issue 12 (14th March 2013) - Bahrami, Kiumars; Khodaei, Mohammad M.; Abbasi, Jamshid
Abstract A highly selective, simple, mild, fast, and clean synthesis of the title compounds is reported by using a commercially available inexpensive catalyst.